CRIMINAL LIABILITY FOR PERSONS OF CRIMINAL ACTION OF HAND PHONE PROCEEDINGS FROM A CRIME BASED ON DECISION NUMBER 1870/Pid.B/2022/PN SURABAYA - kambali, lukas; Pramesti, Wahyu (Jurnal Independent, 2023)
The crime of extortion or the crime of facilitating this is a crime that is closely related to the crime of destroying other peopleâ€™s assets. The crime of extortion or the crime of facilitating this is regulated in the title XXX, Book II in Article 480 of the Criminal Code (KUHP). Withholding as described in the article can be said to be an act of â€œconspiracyâ€. The act of receiving objects obtained because of a crime is not seen as a crime that stands alone or as a zelfstandig misdrijft, but as an act of helping to commit a crime or as a medeplichtigheid in a crime, that is, by which act the perpetrator can obtain the objects obtained. from crimeÂ The main issues that will be discussed in writing this thesis are how criminal responsibility is for the perpetrators of criminal acts of receiving cellphones as the result of a crime based on Decision Number 1870/Pid.B/2022/PN Surabaya and what are the legal considerations of judges in deciding the perpetrators of criminal acts of collecting cellphones proceeds from a crime based on Decision Number 1870/Pid.B/2022/PN Surabaya.Based on this normative juridical research approach is used Using the case approach (Case Approach) aims to study the application of legal norms or rules carried out in legal practice. Especially regarding cases that have been decided as can be seen in the jurisprudence of cases that are the focus of research. The case approach (Case Approach) is used by practitioners in conducting research by identifying court decisions that have qualified jurisprudence to be used in concrete cases. Furthermore, the statutory approach (Statute Approach), this approach is carried out by examining all laws and regulations that are related to the problems (legal issues) that are being faced.In the crime of collection, the perpetrator already knows or should suspect that the item or object is the result of a crime. Meanwhile, the motive of the intermediary acts almost always to enrich oneself in one way or another that cannot be allowed, so to take advantage of other people's crimes. The intermediary is always related to goods "obtained from crimeÂ Â